International food law how food law can balance health, environment and animal welfare - Caporale, Cinzia; Pavone, Ilja Richard; Ragionieri, Maria Pia (Energy and environmental law & policy series ;, 2021)
"This book critically analyses under an ethical and legal point of view if the current food production process based on the industrialization of agriculture and over-exploitation of natural resources is appropriate to guarantee sustainable development, respectful of the right to adequate nutrition of future generations. The growth of the world population and the major request for nutriments raises the issue of how to conciliate the right to food with the protection of the environment and biodiversity, of human health and animal welfare. Few aspects of today's food system demand such an urgent response as our ability to produce sustainable nutrition. Yet at the same time as malnutrition plagues the world, overuse of land, water, and energy in the agricultural and livestock sectors exacerbates environmental degradation and climate change. This book focuses on the interrelation between food law, environmental law, and animal law, and investigates the main legal issues related to food regulation in a global context"--Provided by the publisher.